Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/jfbc.12009
|View full text |Cite
|
Sign up to set email alerts
|

Light Wavelengths Regulate Growth and Active Components of Cordyceps militaris Fruit Bodies

Abstract: Cordyceps militaris is widely cultivated for functional food in China and Southeast Asia. Daylight was commonly used for development of C. militaris fruit bodies. In this study, effects of light wavelengths (pink light = 1/3,450–460 nm + 2/3,620–630 nm; red light = 620–630 nm; blue light = 450–460 nm) on fruit body's production and contents of bioactive components were investigated. The results are: pink light increased dried matter contents and bioefficiency of fruit bodies to the highest (40.06/6.77%) compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 25 publications
0
19
0
3
Order By: Relevance
“…The combination of red and blue light provided better excitation of photoreceptors including phytochromes, cryptochromes, and phototropins, and resulted in higher photosynthetic activity than plants under either monochromatic red or blue light [36]. Dong et al [37] reported that combined red and blue light (1/3 blue light at 450−460 nm + 2/3 red light at 620−630 nm, at 400 lx and 12-h photoperiod for 60 days) increased the DW and bioefficiency of Cordyceps militaris mushroom compared with blue light alone, red light alone, and sunlight. For most species, combined light wavelengths with a large proportion of red light supplemented with blue light significantly increased plant yield [16].…”
Section: Red And/or Blue Lightmentioning
confidence: 99%
“…The combination of red and blue light provided better excitation of photoreceptors including phytochromes, cryptochromes, and phototropins, and resulted in higher photosynthetic activity than plants under either monochromatic red or blue light [36]. Dong et al [37] reported that combined red and blue light (1/3 blue light at 450−460 nm + 2/3 red light at 620−630 nm, at 400 lx and 12-h photoperiod for 60 days) increased the DW and bioefficiency of Cordyceps militaris mushroom compared with blue light alone, red light alone, and sunlight. For most species, combined light wavelengths with a large proportion of red light supplemented with blue light significantly increased plant yield [16].…”
Section: Red And/or Blue Lightmentioning
confidence: 99%
“…Light and other factors also affected the contents of adenosine, cordycepin, d ‐mannitol and exopolysaccharide . Pink light proved to be optimal for cordycepin accumulation . There are many reports on improving cordycepin production by various factors.…”
Section: Discussionmentioning
confidence: 99%
“…광원 중 pink light이 cordycepin 생산능을 증가시켰고 생산 목표 물질에 따라 광원을 선택해야 함도 확인되었다 [31]. CM 동충하초 균 사체 성분분석을 행한 바 핵산물질과 아미노산 함량이 높게 나타나 아마노산 함유 식품개발에 활용도가 기대된다 [88].…”
Section: 배지 균사체 및 자실체 생산unclassified